PENDIDIKAN MULTIKULTURALISME UNTUK MEWUJUDKAN HARMONI SOSIAL - Shinta, Jeesica; Albina, Meyniar (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This research aims to find out multiculturalism education in realizing social harmony in Indonesia. The method used in the research is the literature research method. The data collected and analyzed are taken based on literature readings such as books, journals and other relevant research relevant to this research. While the data collection technique used is a literature study by looking for research data relevant to the discussion relating to multicultural education as an effort to strengthen unity and integrity. The results obtained after conducting the research show that multiculturalism education is able to instill the values of tolerance, mutual respect, and togetherness, which are important foundations for creating social harmony. However, its implementation faces various challenges, such as a lack of understanding of the concept of multiculturalism, limited learning facilities, and exclusive attitudes in the community. To overcome these challenges, teacher training, development of local culture-based teaching materials, intercultural dialogue and inclusive use of digital technology are needed. With the right approach, multiculturalism education can be an effective instrument in building an inclusive, harmonious and united society. Keywords: Multiculturalism Education, Social Harmony, Cultural Diversity, Inclusiveness.